A scientific note of pest-insects associated with stingless bee hive Melipona eburnea in the Ecuadorian Amazon Region - Valdivieso Rivera, Fernando (2021)
Bees are the primary pollinators in nature. However, climate change, excessive use of fertilizers and invasive species have caused the decline of bee colonies. Therefore, this study aimed to analyze the presence of pests in colonies of Melipona eburnea. For this, the colonies of M. eburnea were examined during the honey extraction process. We found 4 different pests associated with the physical conditions of colonies and the fragile defense of the bees against the invaders. In conclusion, this report of the presence of pests is to alert researchers and meliponicultures to prevent the decline of stingless bees.